PENGARUH KEGIATAN KEPRAMUKAAN TERHADAP PENGETAHUAN KEWARGANEGARAAN (CIVIC KNOWLEDGE) MAHASISWA DI UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Efi Miftah Faridli (Universitas Muhammadiyah Purwokerto, 2018)
This research entitled Influence of Scouting Activity on Civic Knowledge Student at Muhammadiyah University of Purwokerto. The purpose is to study how the influence of Scouting Activities at Muhammadiyah University of Purwokerto to Knowledge of student's citizenship. The method used is descriptive research method, weighting score (Weighted Mean Score), correlation test r and t test analysis. This research was conducted to members of Scout Movement active in Front Cluster Banyumas 08.2683-08.2684 University of Muhammadiyah Purwokerto counted 41 people. Based on the results of data processing known that Scouting Activity effect of 75.8%. on the Knowledge of Citizenship, the remaining 24.2% is influenced by other factors not examined. Suggestion from the researcher, it is expected to be the input for the implementers of Scouting activities in this case the Front Line so that better in preparing this activity should be more coordinated with the related parties, such as: the trainers who must be more proactive in this activity, the committee as a whole to improve the quality of its work in preparing these activities. Keywords: scouting, scout movements, civic knowledge